Analisis pengaruh dana pihak ketiga dan pembiayaan perbankan syariah terhadap pertumbuhan ekonomi Indonesia tahun 2011-2021 - Arum, Yasmine Sekar; Himmati, Risdiana (Journal of Accounting and Digital Finance, 2021)
As a financial institution, banks have a crucial role in the Indonesian economy to improve people's living standards through the intermediation function in raising funds from the community and channeling funds to the community. This function in Islamic banking is carried out with third-party funds and financing. The purpose of this study is to find out the influence of third-party funds and Islamic banking financing on Indonesia's economic growth. This research uses a quantitative approach using secondary data (time series), namely third-party fund data and financing, namely mudharabah financing, musyarakah, murabahah, istishna', and qard from Islamic Banking Statistics by OJK and Gross Domestic Product data by BPS from the first quarter of 2011 to the second quarter of 2021. Researchers used the Error Correction Model (ECM) analysis technique in the analysis. The results of this study are variables that affect economic growth in the long term: mudharabah financing and musyarakah, while in the short term is mudharabah financing. Variable third-party funds, murabahah, istishna' and qard do not affect economic growth in the short and long term.